Micro-patterning of Indium thin film for generation of micron and submicron particles using femtosecond laser-induced forward transfer. (28th May 2015) - Alti, Kamlesh; Dwivedi, Sudhanshu; Chidangil, Santhosh; Mathur, Deepak; Khare, Alika
Abstract This paper reports on micro-pattering of Indium thin film (donor substrate) using a higher deposition dose than previously reported. The threshold deposition dose required for micro-patterning was measured. Ejected material from the micro-patterned thin film was deposited onto an accepter substrate kept in close proximity; it clearly shows deposition of micron and submicron particles of Indium. Moreover, a clean line like structure was deposited onto the accepter substrate when the accepter substrate was moved with the same velocity as that of the donor substrate.